2016
DOI: 10.1073/pnas.1600965113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic neural activity during stress signals resilient coping

Abstract: Active coping underlies a healthy stress response, but neural processes supporting such resilient coping are not well-known. Using a brief, sustained exposure paradigm contrasting highly stressful, threatening, and violent stimuli versus nonaversive neutral visual stimuli in a functional magnetic resonance imaging (fMRI) study, we show significant subjective, physiologic, and endocrine increases and temporally related dynamically distinct patterns of neural activation in brain circuits underlying the stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
167
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(191 citation statements)
references
References 57 publications
21
167
0
3
Order By: Relevance
“…In support of this, our recent work has also shown that those who show sustained prefrontal hypoactivation in response to stress show greater levels of maladaptive coping, including binge alcohol intake (Blaine et al, 2016; Sinha et al, 2016). Thus, binge alcohol intake and alcohol use disorders may develop as a result of dysfunctional stress biology including the HPA axis and the sympathetic nervous system, and PFC dysfunction in response to a feed forward loop of high levels of alcohol intake that leads to greater subjective stress and stress-induced alcohol craving and further increases in alcohol intake.…”
Section: Chronic Stress and Chronic Alcohol Promote Prefrontal Cormentioning
confidence: 80%
See 1 more Smart Citation
“…In support of this, our recent work has also shown that those who show sustained prefrontal hypoactivation in response to stress show greater levels of maladaptive coping, including binge alcohol intake (Blaine et al, 2016; Sinha et al, 2016). Thus, binge alcohol intake and alcohol use disorders may develop as a result of dysfunctional stress biology including the HPA axis and the sympathetic nervous system, and PFC dysfunction in response to a feed forward loop of high levels of alcohol intake that leads to greater subjective stress and stress-induced alcohol craving and further increases in alcohol intake.…”
Section: Chronic Stress and Chronic Alcohol Promote Prefrontal Cormentioning
confidence: 80%
“…Red/yellow, positive correlation; blue/purple, negative correlation. (Reproduced with permission from Sinha et al, 2016, Proceedings of the National Academy of Sciences).…”
Section: Figurementioning
confidence: 99%
“…In contrast, weakened or inverse stressor-evoked connectivity would be represented by overall decreases or more negative correlations between two areas or within network as a whole. The first and most common approach in this line of work is to select a predetermined, anatomical region-of-interest or ‘seed’ (e.g., the amygdala) and then compare the relationships (correlations) between activity in that seed and activity in other brain regions at rest, during a stressor task, or during stressor recovery (e.g., Fan et al, 2015; Sinha et al, 2016). Studies using these network-based approaches typically examine how groups of brain areas are altered by stressor tasks, but they have rarely measured how individual differences in peripheral physiological (e.g., HR, BP) responses relate to network-level or connectivity changes.…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rmentioning
confidence: 99%
“…Studies using these network-based approaches typically examine how groups of brain areas are altered by stressor tasks, but they have rarely measured how individual differences in peripheral physiological (e.g., HR, BP) responses relate to network-level or connectivity changes. For example, using a seed-based approach Sinha and colleagues (2016) demonstrated that viewing aversive pictures increased the functional connectivity (cross-correlation) between vmPFC activity and the left anterior PFC, dorsolateral PFC, and inferior parietal lobe. As another example, using a seed-based approach, Gianaros and colleagues (2012) demonstrated that functional connectivity of a canonical visceral control area, the anterior insula (Oppenheimer & Cechetto, 2016), was increased during a psychological stressor that increased BP and decreased cardiovagal baroreflex sensitivity.…”
Section: Brain-imaging Studies Of Stressor-evoked Cardiovascular Rmentioning
confidence: 99%
“…The arcuate nucleus of the hypothalamus contains distinct populations of neurons, which contain appetite stimulators NPY and AgRP. This linkage of systems is highly influenced by long-term stress resulting in altered physiological parameters and causes excessive weight gain leading to obesity [29-35]. …”
Section: The Impact Of Psychosocial Stress and Glucocorticoids On Bodmentioning
confidence: 99%